HIV risk perception, actual HIV risk, sexual risk behaviours, and oral PrEP continuation at the 1-month follow-up in pregnant women not living with HIV in Cape Town, South Africa: A mediation analysis - Moeletsi, Kgotlaganyo (Department of Public Health and Family Medicine, 2025)
Adolescent girls and young women (AGYW) of reproductive age in South Africa are heavily burdened with HIV. If taken effectively, oral preexposure prophylaxis (PrEP) prevents HIV acquisition in pregnant women without HIV. We investigated factors associated with oral PrEP continuation at the 1- month follow-up and the role of HIV risk perception and actual HIV risk in motivating oral PrEP continuation in pregnant women. Data from a cohort of pregnant and postpartum women without HIV in Cape Town, South Africa (PrEP-PP), were analysed using logistic regression models and mediation analysis to assess factors associated with oral PrEP continuation at 1-month and the extent to which HIV risk perception and actual HIV risk explain the relationship between sexual risk behaviours and oral PrEP continuation. Of the 1349 pregnant women enrolled, 84% initiated PrEP at the first antenatal care (ANC) visit. Unemployment (aOR=1.33; 95% CI=1.03-1.73), inconsistent condom use during sex (aOR=0.49; 95%CI=0.22-1.00), having a partner living with HIV/unknown HIV status partner (aOR=1.33; 95% CI=1.00-1.77), being at a medium-to-high risk of acquiring HIV (aOR=1.34; 95% CI=1.00-1.78), STI diagnosis at baseline (aOR=1.30; 95% CI=0.98-1.72), and having no current sex partner (aOR=1.63; 95% CI=0.95-2.89) were associated with oral PrEP continuation at 1-month follow up. Using condoms sometimes during sex (aOR=0.53; 95% CI=0.23-1.12) and being unmarried/not cohabiting (aOR=1.25; 95% CI=0.95-1.66) were marginally associated with oral PrEP continuation. Two-thirds of women misclassified their perceived HIV risk as being at low-risk despite reporting condomless sex or having a partner living with HIV/unknown HIV status partner, highlighting the discordance between actual and perceived HIV risk. The actual HIV risk partially explained the relationship between sexual risk behaviours and oral PrEP continuation at 1-month. Future research is needed on improving accurate assessments of HIV risk to improve PrEP continuation in pregnancy and postpartum.